Fluorescent LDPE and PLA nanocomposites containing fluorescein-modified layered double hydroxides and their ON/OFF responsive behavior towards humidity. (February 2018) - Coiai, Serena; Javarone, Stefano; Cicogna, Francesca; Oberhauser, Werner; Onor, Massimo; Pucci, Andrea; Minei, Pierpaolo; Iasilli, Giuseppe; Passaglia, Elisa
Graphical abstract: Highlights: Fluorescein co-intercalated LDH samples by anion exchange and calcination-rehydration. Transfer of fluorescent features from hybrid particles to PLA and LDPE based nanocomposites. Responsiveness of polymer nanocomposites to wet and dry conditions for designing possible optical humidity indicators. Abstract: We report on the preparation and characterization of fluorescent polymer nanocomposites based upon poly(lactic acid) (PLA) or linear low density polyethylene (LDPE) filled with 5 wt% of fluorescein-modified layered nanoparticles. Modified layered double hydroxide (LDH) nanoparticles were prepared by co-intercalation of fluorescein and alkyl sulfate anions thus yielding to three hybrid samples having different lambda of emission and quantum yield, depending on fluorophore content and presence of dye aggregates. Further separation of Flu aggregates by dispersion of less fluorescent co-intercalated LDHs in PLA and LDPE resulted in an increase of the quantum yield, with better results for PLA-based nanocomposites in agreement with a better morphology. Preliminary data indicated the possible use of these materials as ON/OFF humidity indicators.